Progesterone promotes embryo adhesion by upregulating c-Fos/c-Jun transcription factor-mediated poFUT1 expression. Issue 4 (1st July 2019) - Cui, Xinyuan; Sun, Jiaqi; Liang, Caixia; Zheng, Qin; Yang, Xuesong; Liu, Shuai; Yan, Qiu
Abstract: The proliferation and adhesion abilities of placental trophoblasts are critical for embryo implantation and successful pregnancy. Protein O-fucosyltransferase 1 (poFUT1) and the transcription factor c-Fos/c-Jun have been found to promote trophoblastic cell invade into the endometrium. Progesterone is critical to the regulation of embryonic implantation. However, the exact role of poFUT1 in embryo proliferation and adhesion to the endometrium, and the relationship between progesterone, c-Fos/c-Jun, and poFUT1 has not been studied in detail. In the current study, we found that the serum levels of poFUT1 and progesterone significantly was decreased in miscarriage patients compared with those in normal pregnancy women, and there is a positive correlation between the changes in progesterone and poFUT1. Employing a human embryo trophoblastic cell line (JAR), we showed that progesterone facilitated the activation of c-Fos/c-Jun. Using an electrophoretic mobility shift assay and chromatin immunoprecipitation, we confirmed that the specific transcription factor c-Fos/c-Jun regulated the poFUT1 promoter, which could enhance poFUT1 transcriptional activity, thus further increasing trophoblast cell proliferation and adhesion potential. Taking these findings together, progesterone upregulates poFUT1 expression via the specific transcription factor c-Fos/c-Jun, and then increase trophoblast cell proliferation and adhesion potential. poFUT1 and progesterone may be used together as potential markers of miscarriage, and they may be diagnostic and therapeutic targets for miscarriage. Abstract : Summary Sentence Serum levels of progesterone and poFUT1 significantly decrease in miscarriage patients compared with those in normal pregnancy women, and there is a positive correlation between the changes in poFUT1 and progesterone. Progesterone upregulated poFUT1 expression via the specific transcription factor c-Fos/c-Jun, and then increased trophoblast cell proliferation and adhesion potential. poFUT1 and progesterone may be used together as potential markers of miscarriage, and they may be diagnostic and therapeutic targets for miscarriage.